Viral Etiology of acute respiratory tract infections in hospitalized children and adults in Shandong Province, China - Liu, Ti (Virol J, 2015)
BACKGROUND: The dominant viral etiologies responsible for acute respiratory infections (ARIs) are poorly understood, particularly among hospitalized patients. Improved etiological insight is needed to improve clinical management and prevention of ARIs. METHODS: Clinical and demographic information and throat swabs were collected from 607 patients from 2011 to 2013 in Shandong Province, China. Multiplex RT-PCR (SeeplexTM RV detection, Seegene) was performed to detected 12 respiratory viral pathogens. RESULTS: A total of 607 hospitalized patients were enrolled from 2011 to 2013. Viruses were identified in 35.75 % (217/607) of cases, including 78 influenza virus A and B (IVA and IVB), 47 para-influenza viruses (PIVs), 41 respiratory syncytial virus (RSV) and 38 adenovirus (ADV). For the children under 15 year old, the common detected viruses were influenza viruses, RSV, PIVS and ADV, while the principal respiratory viruses were human coronaviruses (HCoV), PIVs, influenza viruses for the old adults. Co-infections with multiple viruses were detected in 15.67 % of patients. Children under 5 years were more likely to have one or more detectable virus associated with their ARI. The peak of ARI caused by the respiratory viruses occurred in winter. CONCLUSION: This study demonstrated respiratory viruses were the major cause of hospitalized ARI patients in Shandong Province, influenza virus was the most common detected, RSV was the highest incidence among the young children (≤5 years). These findings also gave a better understand of virus distribution among different age and seasons, which help to consider potential therapeutic approaches and develop effective prevention strategies for respiratory virus infection.